Silencing of the UCHL1 gene in giant cell tumors of bone - Fellenberg, Jörg; Lehner, Burkhard; Witte, Daniela (International journal of cancer, 2010)
Giant cell tumors are heterogeneous tumors consisting of multinucleated giant cells, fibroblast-like stromal cells and mononuclear histiocytes. The stromal cells have been identified as the neoplastic cell population, which promotes the recruitment of histiocytes and the formation of giant cells. Strong evidence exists that these cells develop from mesenchymal stem cells (MSCs) but little is known about the molecular mechanisms involved in GCT tumorigenesis. The aim of our study was the identification of cancer-related genes differentially expressed in GCTs compared to MSCs in order to identify possible targets for aberrant promoter methylation, which may contribute to MSC transformation and GCT development. Gene expression of 440 cancer-related genes was analyzed by DNA microarrays in GCT stromal cells and bone marrow-derived MSCs (BMSCs) isolated from the same patient (n = 3) to avoid interindividual variations. Differential expression was identified for 14 genes, which could be confirmed by quantitative PCR in further 21 GCT and 10 BMSC samples. The most pronounced difference in gene expression was detected for UCHL1, an important regulator of the ubiquitin proteasome pathway. Methylation-specific PCR and bisulfite sequencing revealed a strong methylation of the CpG island covering the UCHL1 promoter in GCT stromal cells, whereas methylation was completely absent in BMSCs. UCHL1 expression in stromal cells could be restored by the methylation inhibitor 5-aza-dC. These data demonstrate that the UCHL1 gene is inactivated in GCTs but not in MSCs, suggesting a possible role of UCHL1 in MSC transformation and GCT development.